Nucleocapsid and spike antibody responses following virologically confirmed SARS-CoV-2 infection: an observational analysis in the Virus Watch community cohort. (October 2022) - Navaratnam, Annalan M D; Shrotri, Madhumita; Nguyen, Vincent; Braithwaite, Isobel; Beale, Sarah; Byrne, Thomas E; Fong, Wing Lam Erica; Fragaszy, Ellen; Geismar, Cyril; Hoskins, Susan; Kovar, Jana; Patel, Parth; et al.
Highlights: If infection was confirmed by PCR, 80% of individuals were positive for nucleocapsid antibody. The median nucleocapsid antibody level peaked between days 90 and 119 after infection. Waning levels occurred after 120 days but were earlier for females and younger age categories. Vaccination status before infection may reduce positivity. Abstract: Objectives: Seroprevalence studies can provide a measure of SARS-CoV-2 cumulative incidence, but a better understanding of spike and nucleocapsid (anti-N) antibody dynamics following infection is needed to assess the longevity of detectability. Methods: Adults aged ≥18 years, from households enrolled in the Virus Watch prospective community cohort study in England and Wales, provided monthly capillary blood samples, which were tested for spike antibody and anti-N. Participants self-reported vaccination dates and past medical history. Previous polymerase chain reaction (PCR) swabs were obtained through Second Generation Surveillance System linkage data. The primary outcome variables were seropositivity and total anti-N and spike antibody levels after PCR-confirmed infection. Results: A total of 13, 802 eligible individuals provided 58, 770 capillary blood samples. A total of 537 of these had a previous positive PCR-confirmed SARS-CoV-2 infection within 0-269 days of antibody sample date, among them 432 (80.45%) having a positive anti-N result. Median anti-N levels peaked between days 90 and 119 after PCR results and then began to decline. There is evidence of anti-N waning from 120 days onwards, with earlier waning for females and younger age categories. Conclusion: Our findings suggest that anti-N has around 80% sensitivity for identifying previous COVID-19 infection, and the duration of detectability is affected by sex and age.